2008
DOI: 10.1002/jts.20338
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in bereaved parents

Abstract: The Posttraumatic Growth Inventory (PTGI), Revised Grief Experience Inventory, and World Assumptions Scale were administered to 111 bereaved parents. The PTGI scores indicate that many bereaved parents report personal growth in domains outlined by L.G. Calhoun and R. G. Tedeschi (2001). Grief intensity was inversely correlated with growth scores. Self-worth was a strong predictor of growth scores, whereas assumptions about the benevolence and meaningfulness of the world were not correlated with growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 17 publications
3
94
1
1
Order By: Relevance
“…Buchi et al (2007) found a positive association between grief and growth scores, when the Hospital Anxiety and Depression Scale scores were controlled. In a hierarchical multiple regression analysis, Engelkemeyer and Marwit (2008) found that grief intensity accounted for only 4% of the variance of post-traumatic growth scores in their study. Gerrish et al (2014) reported that women who experience high, but not overwhelming, levels of grief also experienced more growth.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Buchi et al (2007) found a positive association between grief and growth scores, when the Hospital Anxiety and Depression Scale scores were controlled. In a hierarchical multiple regression analysis, Engelkemeyer and Marwit (2008) found that grief intensity accounted for only 4% of the variance of post-traumatic growth scores in their study. Gerrish et al (2014) reported that women who experience high, but not overwhelming, levels of grief also experienced more growth.…”
Section: Resultsmentioning
confidence: 90%
“…They suggested that, potentially, individuals who had chosen to engage in support networks may not be representative of fathers who do not chose to engage in social support networks (Polatinsky & Esprey, 2000). Similarly, some authors reported that PTGI scores (Engelkemeyer & Marwit, 2008) or reports of benefit-finding (Bogensperger & Lueger-Schuster, 2014) did not differ between mothers and fathers.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…There is evidence that some individuals experience post-traumatic growth following bereavement (Engelkemeyer & Marwit, 2008; Gamino, Sewell, & Easterling, 2000; Michael & Cooper, 2013). Importantly, Calhoun, Tedeschi, Cann, and Hanks (2010) emphasize that post-traumatic growth in the context of grief occurs from the struggle with bereavement, and that it would be a gross misinterpretation to suggest that focusing on growth minimizes the importance of attending to coexisting negative reactions.…”
Section: Introductionmentioning
confidence: 99%